UJI KEEFEKTIFAN PENGGUNAAN MEDIA PEMBELAJARAN VIDIO ANIMASI “LAYAR HISTORY” MATERI SEJARAH KELAHIRAN PANCASILA PADA PESERTA DIDIK KELAS V SDN KENITEN 1 - Isdela Oktovi Budiawati; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted from the results of observations during the Pancasila Education learning, the history of the birth of Pancasila material implemented at SDN Keniten 1. In grade V students there are problems, namely they have difficulty understanding abstract material and the learning outcomes obtained from daily tests are still relatively low or below the Learning Objective Achievement Criteria (KKTP) which is below 75. The purpose of this study was to determine the effectiveness of the animated video learning media